5I*Performance indicators of machining and operations management systems - (:unkn) unknown (IEEE, 2009)
Operations management in manufacturing systems mainly deals with five capabilities including monitoring, analysis, decision making, communications and controls, in which the group of capabilities run in a closed-loop cycle. There is no guarantee that these functions will be executed in the order expected. This necessitates a close control over the capabilities of manufacturing system in order to make sure that the inputs are ready to be utilised on time. This surely brings up the question of the performance of machining and operations management which was dealt with in different ways so far. In this paper 5I* approach is presented taking the integrity, intelligence, informative aspects and innovative capabilities as well as irreproachable manufacturing characters into account. The paper describes 5I* and its sub components.